Effects of montelukast on airway narrowing from eucapnic voluntary hyperventilation and cold air exercise - Rundell, K (BMJ Group, 2005)
Background: Exercise induced bronchoconstriction (EIB) is common in elite athletes. Eucapnic voluntary hyperventilation (EVH) is a laboratory test recommended for the identification of EIB in athletes, secondary to a field exercise challenge. Montelukast attenuates EIB, but its protective effect against airway narrowing from EVH has not been investigated. Objective: To examine the effectiveness of montelukast after exercise and after EVH. Methods: A randomised, placebo controlled, double blind, crossover study was performed with 11 physically active EIB positive subjects (eight men, three women; mean (SD) age 22.8 (6.8) years). Six hours before each of the following challenges 10 mg montelukast or placebo was ingested: (a) a six minute, cold air (–3°C) maximal effort work accumulation cycle ergometer exercise; (b) EVH, breathing 5% CO(2) compressed air at 85% maximal voluntary ventilation for six minutes. Spirometry was performed before and 5, 10, and 15 minutes after the challenge. At least 48 hours was observed between challenges. Results: No differences in forced expiratory volume in one second (FEV(1)) were found after the two challenges. Exercise and EVH resulted in falls in FEV(1) of 22.4 (18.0) and 25.6 (16.8) respectively. Falls in FEV(1) after montelukast were less than after placebo (10.6 (10.6) and 14.3 (11.3) after exercise and EVH respectively; p<0.05). Montelukast provided protection against bronchoconstriction (59% and 53%; p<0.05) for eight exercising subjects and 10 EVH subjects; no protection was afforded for three exercising and one EVH challenged subject. Conclusions: Both exercise and EVH were potent stimuli of airway narrowing. A single dose of montelukast provided reasonable protection in attenuating bronchoconstriction from either exercise or EVH. The similar protection by montelukast suggests that EVH is a suitable laboratory surrogate for EIB evaluation.